Ghana Irrigation Sector Mapping - Delinthe, Luken; Zwart, Sander J. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The irrigation sector of Ghana was mapped with the purpose to inform private sector parties on the potential for developing small-scale irrigation. It is shown that offcial schemes only amount 17,000 ha, wheras the area under farmer-led irrigation development is estimated 189,000 ha. Large potentials remain untapped and another 700,000 households could benefit from support to invest in irrigation equipment. The reports shows key information in figures, maps and other visuals.